Teachers’ Technological Self-Efficacy sebagai Determinan Adopsi Teknologi oleh Guru: Tinjauan Sistematis Berbasis Model Penerimaan Teknologi - Eko Nurhaji Purnomo; Lestari Eko Wahyudi; Aan Fardani Ubaidillah (Journal of Mandalika Literature, 2026)
The digital transformation of education positions Teachers’ Technological Self-Efficacy (TTSE) as a critical factor influencing teachers’ success in adopting technology. This study presents a systematic review of 136 publications published between 2005 and 2025 to map the development of TTSE research and examine its role as a key determinant of technology adoption within the Technology Acceptance Model (TAM). The findings indicate a substantial increase in TTSE-related studies, particularly after 2020, with major contributions originating from Turkey, China, and the United States. However, no single author or institution dominates the field, suggesting that research on TTSE remains widely distributed and continues to evolve. The results show that TTSE strongly predicts teachers’ intentions and behaviors in adopting technology, particularly through its influence on perceived ease of use (PEU) and perceived usefulness (PU)as conceptualized in TAM. Furthermore, technology training, digital experience, and institutional support are identified as significant factors that enhance TTSE. This review underscores that strengthening TTSE is essential to promoting effective technology integration in teaching and should be prioritized in policy, professional development, and teacher education programs. The study further reinforces TAM’s relevance in explaining the mechanisms underlying teachers’ technology adoption